Follow-Up of the Novel Free Margin Running Suture Technique for Mitral Valve Repair - Agnino, Alfonso; Lanzone, Alberto Maria; Albertini, Andrea; Anselmi, Amedeo (The Thoracic and Cardiovascular Surgeon, 2019)
The free margin running suture (FMRS) is a novel technique for nonresection correction of degenerative mitral regurgitation. It was employed in 37 minimally invasive mitral repair cases. We performed a retrospective collection of in-hospital data and a clinical/echocardiographic follow-up. All patients were discharged with none or mild mitral regurgitation, except one who had mild-to-moderate (2+) regurgitation. At follow-up (average: 2.1 years), all patients were alive; there were no instances of recurrent regurgitation, one case of 2+ regurgitation, and no valve-related complications. Average mitral valve area, mean gradient, and coaptation length were 2.9 cm2 ±0.1, 3.5 mm Hg ±0.9, and 1.1 cm ±0.2.
Keywords: mitral valve repair; minimally invasive surgery; outcomes